MiR‐345‐5p regulates proliferation, cell cycle, and apoptosis of acute myeloid leukemia cells by targeting AKT2. Issue 2 (2nd October 2018) - Ying, Xiaoyang; Zhang, Wanggang; Fang, Meiyun; Zhang, Weijun; Wang, Chenchen; Han, Li
Abstract: Acute myeloid leukemia (AML) is a malignant clonal hematopoietic disease, which is caused by hematopoietic stem cell abnormalities. Epigenetic regulation, especially of microRNAs (miRNAs), mostly results from external or environmental effects and is critical to AML. In this study, for the first time, we report that decreased expression of miR‐345‐5p facilitates the proliferation of leukemia cells in AML. Further study demonstrated that AKT1/2 was the target of miR‐345‐5p and was responsible for the dysregulation of leukemia cell proliferation and apoptosis. Inhibition of AKT1/2 ameliorated this malignant effect, which provides new insight into AML diagnosis, treatment, prognosis, and next‐step translational investigations. Abstract : We reported that decreased expression of miR‐345‐5p facilitated leukemia cells proliferation in acute myeloid leukemia (AML). AKT1/2 was the target of miR‐345‐5p and responsible for dysregulation of leukemia cells proliferation and apoptosis. Inhibition of AKT1/2 could ameliorated this malignant effect and provide a new insight into AML diagnosis, treatment, prognosis, and next‐step translational investigations.